Os obstáculos ao desenvolvimento da negociação coletiva - Mendes, Felipe Prata (2022)
This work aims to explore the deadlocks on improving collective negotiation in Brazil and also tries to show paths to overcome the impasses found. Fulfilling the task demands to grasp collective negotiation as a human and fundamental right. Next, the work presents the factors able to reveal how collective negotiation is essential to labor relationships and also seeks to display its grounds, such as trade union freedom and collective private autonomy. Facing the research problem entails analyzing the consequences brought about the labor legislative reform, in order to ascertain if the reform embodies a negative element that deters the flourishing of collective negotiation. Conclusions achieved proves the labor reform is not the great obstacle against collective negotiation in Brazil, which can only be improved through a trade union reform that ensures full freedom of association. An indispensable element for advancing collective negotiation is diminishing judicial intervention, which should respect the principle of minimal interference on collective autonomy. Other elements to consider are refreshing the content discussed in negotiations and also the digital inclusion of trade unions. The research developed is theoretical and normative